Collaborative writing and process writing approach: The effect and students perception - Winarti; Cahyono, Bambang Yudi (Universitas Muhammadiyah Sidoarjo, 2020)
Over the last few years, the researchers and practitioners have acknowledged the potential benefits attained from collaborative writing activity which was based on the well- known theories of social constructivist and output hypothesis. Grounding from these theories, this study examined the collaborative writing combined with writing process approach to find out the effect of the task on students' ability in writing an explanation essay and students perception about the task. Two intact classes involving 30 students in each class participated in this study. One class as the experimental group completed the writing task using process writing in pairs while the other class completed the task individually. The students in experimental group were given a questionnaire right after the treatment to pool their views on the task. Post-test by administering the writing test was conducted to see the effect of the treatment. Data analysis revealed that students employing collaborative writing using process writing had better writing ability than students working individually. It was also found that most students felt that they gained many benefits from doing collaborative writing. These findings suggested that collaborative writing combined with process writing can be implemented in EFL writing pedagogy to improve students' writing ability. HIGHLIGHTS 1. Collaborative writing has the positive effect on the overall writing ability and on each element of writing skill.2. Collaborative writing not only encouraged the students to share the knowledge they had to other members but also it gave them remarkable input they needed in improving thewriting skill.